Bioethanol Production from Sago Waste as Renewable Energy: A Review - Salwa, Nadiatus; Gunawan, Cahyani Eka Putri; Danisa, Fani; Nilnalmuna, Revitalia; Rohmah, Nur (Universitas Negeri Semarang, 2024)
Energy consumption has increased rapidly because the world population has grown, so has energy consumption for industrial needs. Now Indonesia still uses fossil fuels as the main energy source, because of their non-renewable nature, the continuous use of fossil fuels causes scarcity problems. Bioethanol production is currently getting more intense, this is because there are several factors that cause it to be more intense, namely market stability, low costs, sustainability, the composition of alternative energy fuels and the catastrophic depletion of fossil fuels. Sago waste can be used as an environmentally friendly renewable resource. Bioethanol production process from sago waste using enzymes and fermentation with the help of microorganisms. The bioethanol production process from sago waste has four main parts. The first thing to do is the pre-treatment process, namely drying the sago pulp and delignification process. Samples from the delignification process will then be used in the hydrolysis process with a catalyst in the form of HCl. The results of the hydrolysis were fermented at a pH of 5 and tape yeast was added. Then in the distillation process requires filtrate which was then evaluated qualitatively using K2Cr2O7 reagent. The mixture derived from the fermentation process using baker's yeast and wet sago pulp can produce bioethanol levels up to 45.70%. The process of making bioethanol from sago waste through a baker's yeast fermentation process is expected to help advance the bioethanol production process as a renewable energy source in Indonesia.